2011
DOI: 10.1007/s13187-011-0294-z
|View full text |Cite
|
Sign up to set email alerts
|

An Increase in HPV-Related Knowledge and Vaccination Intent Among Parental and Non-parental Caregivers of Adolescent Girls, Age 9–17 Years, in Appalachian Pennsylvania

Abstract: A theory and community-based educational intervention was designed to increase HPV-related knowledge and intent to vaccinate adolescent girls, against human papillomavirus (HPV) in Appalachia, a region with high cervical cancer incidence and mortality. An HPV educational session was conducted with immediate pre-/post-test questionnaires and 1-month follow-up telephone interview. McNemar tests and paired t tests evaluated change in individual knowledge variables and change in overall knowledge and intent to vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 12 publications
2
41
0
Order By: Relevance
“…Spleen et al tested the effectiveness of a 1-h slide presentation about HPV infection to parents of girls in Appalachian Pennsylvania. This study found increases in scores for intention to accept the HPV vaccine after the presentation of less than 1 point on a 4 point-scale ( P = 0.002) although it should be noted that 31% of the sampled parents had daughters who had already started the HPV vaccination series at the time of the intervention [29]. A study by Kepkaet al [32] tested the effectiveness of a Spanish-language radio advertisement (referred to as radionovela in the study) to educate Latino parents about HPV vaccination.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Spleen et al tested the effectiveness of a 1-h slide presentation about HPV infection to parents of girls in Appalachian Pennsylvania. This study found increases in scores for intention to accept the HPV vaccine after the presentation of less than 1 point on a 4 point-scale ( P = 0.002) although it should be noted that 31% of the sampled parents had daughters who had already started the HPV vaccination series at the time of the intervention [29]. A study by Kepkaet al [32] tested the effectiveness of a Spanish-language radio advertisement (referred to as radionovela in the study) to educate Latino parents about HPV vaccination.…”
Section: Resultsmentioning
confidence: 92%
“…Of these, five were conducted in the United States [2629] and other two were from India [30] and China [31]. Less than half the studies were randomized, controlled trials [27,28,32] with most designed as quasi-experimental comparisons of parental intentions to vaccinate pre- versus post-intervention [26,2931]. All but two of the studies [26,27] exclusively surveyed parents of girls and none of the studies involved any follow-up assessment beyond the period immediately following the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Spleen and colleagues conducted an educational session to increase HPV vaccine knowledge and vaccination intent for parents and caregivers of HPV vaccine-eligible girls in Appalachia. 53 Intention to vaccinate within 1 mo increased significantly among parents post intervention (P D 0.002). Kepka et al evaluated the effectiveness of a culturally-tailored Spanish HPV vaccine awareness program broadcasted as a "radionovella" through a randomized trial.…”
Section: Interventions Focused On Human Papillomavirusmentioning
confidence: 97%